Estratégias no ensino de vestir-se e alimentar-se para uma criança com baixa visão - Villela, Tereza Cristina Rodrigues (2018)
This work had the general objective of identifying and describing the useful resources for teaching dressing and feeding activities for a child with low vision, and the specific objective was to identify and describe the types of resources that help in the necessary skills for the execution of dressing activities (dress dolls, dress up, put shoes on dolls and wear shoes) and feeding ("feeding dolls", set the table, butter, jelly or curd on bread, open cans of juice / put straws in the juice can, open jars of butter, jelly or curd, and peel and cut bananas). Study participants were a five-year-old girl with low vision, her mother - who responded to interviews and participated in two meetings with the child and the researcher. During tasks was analyzed the type of help offered - total help, which included doing the activity by the child; partial physical and oral help, assisting the child in the accomplishment of an activity with his participation; oral help, instructions or explanations of the activity appropriate to the needs of the child; and absence of help, when the adult did not interfere - and the type of performance of the participant; independent, when he performed alone; and refused, when he refused to do the activity. The type of aid most frequently provided was partial aid, and the least frequent aid was total aid. At the end of the meetings the child achieved independent performance in all activities. We emphasize the importance of future studies that investigate other autonomous life activities, with attention to help and information about efficient mediations of the adult to different learning styles of these activities by children with visual impairment.